Time-Dependent Multimode Analysis and Simulation Studies of Gyroklystron Amplifier - Swati, M.V. (My University, 2016)
The horizon of microwave tubes still find its dominance in delivering high power at the millimeter and sub-millimeter wave frequencies, and this is an area where their solid-state counterparts are not able to compete. Miniaturization of the conventional microwave tubes due to wavelength reduction at the millimeter waves result in decrement of the power handling capability of such devices. On the other hand, for quantum-optical devices, like, lasers, it is difficult to sustain the population inversion with the reduction of the energy of each quantum in the lower frequency region. Therefore, during the past few decades, considerable research interest has been aroused in the development of fast-wave devices to bridge the gap between the domain of conventional microwave tubes at low frequencies and the extent of lasers at high frequencies. In the category of gyro-devices, the gyrotron has been most extensively studied, and are commercially available for applications like plasma heating. However, from the standpoint of application in the information carrying systems, like millimeter-wave radar and communication, the gyrotrons are far from being mature, still requiring much improvement with respect to signal coherence and spectral quality. For such applications, gyro-amplifiers such as gyroklystron or gyro-TWT would be a more appropriate choice than an oscillator. In recent years, considerable research and development interest has been aroused in the area of gyroklystron amplifier. The capability of gyroklystron amplifiers to provide high gain and moderate bandwidth are making them attractive as high-power millimeter-wave amplifier. These amplifiers have potential for applications such as millimeter-wave radars, particle accelerators, RF plasma heating systems, etc. The gyroklystron consists of a series of resonant cavities separated by a region called as drift tube like a conventional klystron except that instead of reentrant cavities, overmoded cylindrical cavities are used. Electron beam and RF wave interaction mechanism in the gyroklystron is based on cyclotron resonance maser (CRM) instability similar to that in gyrotrons, instead of Weibel instability as in conventional klystrons. The high frequency gyro-device requires higher magnetic field which is in order to synchronize the frequency of oscillation with the cyclotron frequency. The magnetic field requirement can be reduced through higher cyclotron harmonic operation. Due to higherorder mode operation of the RF interaction circuit, fast-wave devices offer the larger size of the interaction structure in the millimeter-wave frequency range as compared to slowwave devices and hence handle higher power. Additionally, the electron beam location will also be far from the wall of RF interaction structure. At higher frequencies, the gyroklystron operation at higher order modes results in the dense RF spectrum which can cause probability of switching to the unwanted modes. This results into the serious problem of mode competition which affects the performance of the device, such as, efficiency, and RF power etc. Additionally, at higher frequencies, the device operation at higher harmonic modes also results in the mode competition from the nearby higher harmonic competing modes as well as the fundamental harmonic modes.
Keywords: Time-Dependent; Multimode Analysis; Gyroklystron Amplifier